Apatite Glass-Ceramics: A Review - Duminis, Tomas; Shahid, Saroash; Hill, Robert Graham (Frontiers in Materials, 2017)
This article is a review of the published literature on apatite glass-ceramics (GCs). Topics covered include crystallization mechanisms of the various families of the apatite GCs and an update on research and development on apatite GCs for applications in orthopedics, dentistry, optoelectronics and nuclear waste management. Most apatite GCs crystallize through a homogenous nucleation and crystallization mechanism, which is aided by a prior liquid-liquid phase separation. Careful control of the base glass composition and heat-treatment conditions, which determine the nature and morphology of the crystal phases in the GC can produce GC materials with exceptional thermal, mechanical, optical and biological properties. The GCs reviewed for orthopedic applications exhibit suitable mechanical properties and can chemically bond to bone and stimulate its regeneration. The most commercially successful apatite GCs are those developed for dental veneering. These materials exhibit excellent translucency and clinical esthetics, and mimic the natural tooth mineral. Due to the ease of solid solution of the apatite lattice, rare earth doped apatite GCs are discussed for potential applications in optoelectronics and nuclear waste management. One of the drawbacks of the commercial apatite GCs used in orthopedics is the lack of resorbability, therefore the review provides a direction for future research in the field.